Characterization of Forearm Muscle Activation in Duchenne Muscular Dystrophy via High-Density Electromyography: A Case Study on the Implications for Myoelectric Control - Nizamis, Kostas; Rijken, Noortje H. M.; van Middelaar, Robbert; Neto, João; Koopman, Bart F. J. M.; Sartori, Massimo (Frontiers in Neurology, 2020)
Duchenne muscular dystrophy (DMD) is a genetic disorder that results in progressive muscular degeneration. Although medical advances increased their life expectancy, DMD individuals are still highly dependent on caregivers. Hand/wrist function is central for providing independence and robotic exoskeletons are good candidates for effectively compensating for deteriorating functionality. Robotic hand exoskeletons require the accurate decoding of motor intention, typically via surface electromyography (sEMG). Traditional low-density sEMG was used in the past to explore the muscular activations of individuals with DMD, however it cannot provide high spatial resolution. This study characterized for the first time, the forearm high-density electromyograms of three individuals with DMD while performing seven hand/wrist related tasks and compared them to eight healthy individuals (all data available online). We looked into the spatial distribution of HD-sEMG patterns using principal component analysis (PCA), the repeatability and the amplitude distributions. Additionally, we used a machine learning approach, to assess DMD individuals’ potentials for myocontrol. Our analysis showed that although participants with DMD were able to repeat similar HD-sEMG patterns across gestures (similarly to healthy participants), a fewer number of electrodes was activated during DMD participants gestures compared to the healthy participants. Additionally, participants with DMD activated their muscles close to maximal contraction level (0.63±0.23) whereas healthy participants had lower normalized activations (0.26±0.2). Lastly, participants with DMD showed on average fewer principal components (3) explaining 90% of the complete gesture space than the healthy (5). However, the ability of the DMD participants to produce repeatable HD-sEMG patterns was unexpectedly comparable to that of healthy participants and the same holds true for their offline myocontrol performance, disproving our hypothesis and suggesting a clear potential for the myocontrol of wearable exoskeletons. Our findings present evidence for the first time, on how DMD lead to progressive alterations in hand/wrist motor control in DMD individuals compared to healthy. The better understanding of these alterations can lead to further developments for the intuitive and robust myoelectric control of active hand exoskeletons for individuals with DMD.